KONSEP DASAR NILAI - Abdul Wahab Syakhrani; Muhammad Arifin Ilham; Muhammad Hafiz Anshari; Muhammad Riski Amin; Sarif (JIP: Jurnal Ilmu Pendidikan, 2026)
Values are considered important and meaningful elements that serve as guidelines in human life for determining attitudes and behavior. They help individuals distinguish between right and wrong as well as good and bad. Values can be classified into various types, including material, vital, and spiritual values, which encompass truth, beauty, morality, and religion, as well as social, cultural, and religious values. Values play a crucial role for both individuals and society, functioning as a foundation for personality development, social regulation, unity, and the creation of order and harmony. The application of values in daily life, such as honesty, discipline, responsibility, and mutual respect, has a positive impact on individuals and their environment. Therefore, values are an inseparable part of human life in creating a harmonious and meaningful society.